Agenda 2030: a case study on the challenges of implementing SDG 6 for the municipality of Pombal-PB (Research, Society and Development, 2022)
The 2030 agenda is a commitment made by more than 190 nations, being a relevant instrument for the promotion of sustainable development worldwide and consisting of 17 goals, called sustainable development goals (SDGs), which are broken down into 169 goals, where within Of these objectives, SDG 6 deals with Drinking Water and Sanitation, it unfolds several goals. In this sense, this article aims to analyze the achievement of goals 6.1, 6.2, 6.3 aimed at the municipality of Pombal in the state of Paraíba. A case study was used as a methodology, with documentary and exploratory research, as well as a comparative analysis. The results showed that in relation to goal 6.1 the municipality will possibly reach by 2030, in relation to goals 6.2 and 6.3 it will hardly reach, it will take effort, commitment from the public power to reach these goals. In order to achieve all the goals of SDG 6, more investment is needed in these areas, it is important that the government promotes partnerships with the private sphere, non-governmental organizations and civil society. It is noteworthy that investing in basic sanitation is investing in several factors such as health, quality of life of the population and environmental preservation of society.